2005
DOI: 10.1534/genetics.105.046342
|View full text |Cite
|
Sign up to set email alerts
|

An Ancient Mitochondrial Polymorphism in Adalia bipunctata Linked to a Sex-Ratio-Distorting Bacterium

Abstract: Sex-ratio-distorting microbes are common parasites of arthropods. Although the reasons they have invaded and spread though populations are well understood, their subsequent dynamics within those populations are virtually unknown. We have found that different strains of a male-killing Rickettsia bacterium infecting the beetle Adalia bipunctata are associated with distinct mitochondrial haplotypes, which is expected as both the mitochondria and the bacteria are maternally transmitted. These mitochondrial haploty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 59 publications
1
37
1
1
Order By: Relevance
“…For example, Drosophila recens infected with the maternally transmitted Wolbachia shows much lower mtDNA variation than predicted by neutrality, whereas the closely related uninfected Drosophila quinaria has more normal levels of mtDNA. Conversely, Adalia bipunctata is infected with three endosymbiont strains and has highly elevated mtDNA levels, overall, but very low mtDNA levels in beetles infected with a particular endosymbiont strain (Jiggins and Tinsley, 2005).…”
Section: Mtdna and Cpdna Diversitymentioning
confidence: 99%
“…For example, Drosophila recens infected with the maternally transmitted Wolbachia shows much lower mtDNA variation than predicted by neutrality, whereas the closely related uninfected Drosophila quinaria has more normal levels of mtDNA. Conversely, Adalia bipunctata is infected with three endosymbiont strains and has highly elevated mtDNA levels, overall, but very low mtDNA levels in beetles infected with a particular endosymbiont strain (Jiggins and Tinsley, 2005).…”
Section: Mtdna and Cpdna Diversitymentioning
confidence: 99%
“…One aspect that has attracted attention recently is the impact of male-killing infections on the hosts' population genetics. However, almost all studies conducted so far have focused on the population genetics of the mitochondrial genome, because of the obvious impact of disequilibrium with any other maternally inherited agents ( Johnstone and Hurst 1996;Schulenburg et al 2002;Jiggins 2003;Dyer and Jaenike 2004;Hurst and Jiggins 2005;Jiggins and Tinsley 2005). To our knowledge, there is only one study on the impact of male-killing bacteria on the population genetics of nuclear genes (Telschow et al 2006).…”
mentioning
confidence: 99%
“…The mitochondrial haplotype H9, reported in populations of A. bipunctata in the northern part of Europe (Schulenburg et al, 2002;Jiggins & Tinsley, 2005), was found by us in St. Petersburg and Arkhangelsk (Fig. 2).…”
Section: Mitochondrial Haplotype H9mentioning
confidence: 55%
“…These mitochondrial haplotypes, H9 and H10, were considerably different from the other. An attempt to evaluate the time of divergence of the mitochondrial haplotype H10 by Jiggins & Tinsley (2005) gave an age of 2-2.5 million years. Consequently, this mitochondrial polymorphism is referred to as ancient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation